Fighting Dirty : The Inside Story of Covert Operations from Ho Chi Minh to Osama Bin Laden - Harclerode, Peter, 1947- (London Cassell, 2001)
In the wake of the September 11th horror, nothing could be timelier than this exploration of world terrorism and the forces that fight it--armies and missions often shrouded in mystery. A foremost expert on guerrilla warfare presents, for the first time, a comprehensive investigation of covert military operations from Vietnam to Afghanistan. Among the revelations: that the CIA handed out shoulder-fired antiaircraft missiles "like lollipops" to Osama bin Laden and other mujahadeen leaders, weapons they may now turn against us how British SAS operated inside Afghanistan against the Russians and used "former special forces" personnel for clandestine missions why secret militia and locally recruited fighters successfully defeated guerrillas and terrorists in Oman, Malaya, and Borneo, but could not in Indochina and Algeria and how "fighting dirty" sometimes meant helping drug dealers in exchange for their support. Most relevant is the detailed analysis of why Russia failed to conquer Afghanistan, what we can learn from their experience, and the perils awaiting any invader.
Includes Glossary And Index.
Keywords: Special Forces (Military Science) -- Special Operations (Military Science)